Ovarian Sensitivity Decreased Significantly in Patients With Insulin Resistance Undergoing in vitro Fertilization and Embryo Transfer - Zheng, Yanjun; Pan, Ye; Li, Ping; Wang, Zhongyuan; Wang, Ze; Shi, Yuhua (Frontiers in Physiology, 2022)
The ovarian sensitivity could affect the outcome of in vitro fertilization and embryo transfer (IVF-ET). The objective of this study is to explore the relationship between the ovarian sensitivity index (OSI) and traditional ovarian response makers and observe relationship between OSI and insulin resistance (IR). The patients were enrolled in this study which included 131 PCOS with IR patients (PCOS-IR), 52 PCOS without IR patients (PCOS-N), 164 Control with IR patients (Control-IR), 133 Control without IR patients (Control-N), 295 IR patients, 184 Non-IR patients, 183 PCOS patients and 297 Control patients (Non-PCOS patients). All patients received standard long protocol or the gonadotropin releasing hormone (GnRH) antagonist protocol to induce follicles development. The two protocols downregulated the pituitary function or blocked the pituitary luteinizing hormone (LH) secretion with a GnRH antagonist. Both protocols can block premature LH surges, because premature luteinization is not conducive to follicular development. All patients underwent IVF or intracytoplasmic sperm injection (ICSI). Embryo transfer was carried out according to the specific situation of each patient. The OSI was significantly reduced in IR patients. The OSI had significant positive relationship with AMH, AFC, basal LH/FSH, dominant follicles number on trigger day, retrieved oocytes, embryos number and high-quality embryos number. OSI had significant negative relationship with age, BMI, basal FSH, initial dose of Gn, total dose of Gn. The ROC curve of OSI demonstrated a better accuracy in distinguishing patients with positive pregnancy and clinical pregnancy, with an area under the curve (AUC) of 0.662 (95% CI, 0.598-0.727) and 0.636 (95%CI, 0.577-0.695) respectively. Patients could get a higher rate of dominant follicle count (p<0.0001) through the treatment of standard long protocol when compared to GnRH antagonist protocol. The OSI has significant correlation with traditional ovarian response markers and could be a good predictor of positive pregnancy and clinical pregnancy for IR patients.